Placental Iron Content Is Lower than Previously Estimated and Is Associated with Maternal Iron Status in Women at Greater Risk of Gestational Iron Deficiency and Anemia. Issue 3 (7th December 2021) - Barad, Alexa; Guillet, Ronnie; Pressman, Eva K; Katzman, Philip J; Miller, Richard K; Darrah, Thomas H; O'Brien, Kimberly O
ABSTRACT: Background: Based on limited data, it is estimated that the placenta retains 90 mg of iron. Little is known about determinants of placental iron content. Animal data indicate that the placenta prioritizes iron for its own needs, but this hypothesis has not been evaluated in humans. Objectives: To characterize placental iron content and placental iron concentration (p[Fe]) in pregnant women at risk of iron insufficiency and identify determinants of p[Fe]. Methods: Placentas were collected from 132 neonates born to teens carrying singletons (≤18 y) and 101 neonates born to 48 women carrying multiples (20–46 y). Maternal and neonatal iron status indicators [hemoglobin, serum ferritin (SF), soluble transferrin receptor (sTfR), serum iron, total body iron (TBI)] and hormones (erythropoietin, hepcidin) were measured. p[Fe] was measured using inductively coupled plasma–mass spectrometry. Correlation analyses and mixed-effects models were constructed to identify determinants of p[Fe]. Results: Mean placental iron content was 23 mg per placenta (95% CI: 15, 33 mg) in the multiples and 40 mg (95% CI: 31, 51 mg) in the teens ( P = 0.03). Mean p[Fe] did not differ between the cohorts. p[Fe] was higher in anemic (175 μg/g; 95% CI: 120, 254 μg/g) compared with nonanemic (46 μg/g; 95% CI: 26, 82 μg/g) women carrying multiples ( P = 0.009), but did not differ between anemic (62 μg/g; 95% CI: 40, 102 μg/g) and nonanemic (73 μg/g; 95% CI: 56, 97 μg/g) teens. In women carrying multiples, low maternal iron status [lower SF ( P = 0.002) and lower TBI ( P = 0.01)] was associated with higher p[Fe], whereas in teens, improved iron status [lower sTfR ( P = 0.03) and higher TBI ( P = 0.03)] was associated with higher p[Fe]. Conclusions: Placental iron content was ∼50% lower than previously estimated. p[Fe] is significantly associated with maternal iron status. In women carrying multiples, poor maternal iron status was associated with higher p[Fe], whereas in teens, improved iron status was associated with higher p[Fe]. More data are needed to understand determinants of p[Fe] and the variable iron partitioning in teens compared with mature women.